Rekonstruksi Islamisasi Sains Sebagai Langkah Awal Islamisasi Ilmu: Pemikiran Syed Muhammad Naquib Al-Attas - Dody Irawan (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2019)
Muhammad Naquib al-Attas was the first figure who explicitly stated the project of Islamization of knowledge when a conference held in Mecca. In the concept of religion, there are at least several concepts that are contained, namely: faith (belief), Islam (obedience) and Ihsan (integration between heart and mind in good deeds) and all of this, driven by science. Reconstruction of Al-Attas's thinking originated from his concern for the narrowing of meaning to Islamic scientific terms caused by attempts at westernization, mythology, the inclusion of things that are magical and secularism. In line with its strategy of Islamization, al-Attas seems to use the approach of Islamization of science as a springboard to correct modern discipline and purify the sciences that have been contaminated by the ideology of secularism. Knowledge in al-Attas' view is something that is devolved from God to enter into the spirit, then interpreted by the forces that exist in that spirit to the birth of knowledge and forms of symbols or logical proportions or metamatise.